2018
DOI: 10.3390/ijms19092622
|View full text |Cite
|
Sign up to set email alerts
|

p53 Functions in Adipose Tissue Metabolism and Homeostasis

Abstract: As a tumor suppressor and the most frequently mutated gene in cancer, p53 is among the best-described molecules in medical research. As cancer is in most cases an age-related disease, it seems paradoxical that p53 is so strongly conserved from early multicellular organisms to humans. A function not directly related to tumor suppression, such as the regulation of metabolism in nontransformed cells, could explain this selective pressure. While this role of p53 in cellular metabolism is gradually emerging, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 141 publications
(268 reference statements)
6
82
1
Order By: Relevance
“…Zoltan Derdak demonstrated that pharmacologic inhibition of p53 with pifithrin‐α p‐nitro attenuates hepatic steatosis and liver injury in C57BL/6 mice fed HFD for 8 weeks . Moreover, systemic pifithrin‐α administration considerably diminished P53 levels and ameliorated Akt phosphorylation in all peripheral tissues including adipose tissues and alleviated IR . As Mdm2 protein functions as an E3 ubiquitin ligase that inhibits p53 transcriptional activation, the Mdm2 C305F mice are resistant to HFD‐induced obesity and obesity‐associated illnesses .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoltan Derdak demonstrated that pharmacologic inhibition of p53 with pifithrin‐α p‐nitro attenuates hepatic steatosis and liver injury in C57BL/6 mice fed HFD for 8 weeks . Moreover, systemic pifithrin‐α administration considerably diminished P53 levels and ameliorated Akt phosphorylation in all peripheral tissues including adipose tissues and alleviated IR . As Mdm2 protein functions as an E3 ubiquitin ligase that inhibits p53 transcriptional activation, the Mdm2 C305F mice are resistant to HFD‐induced obesity and obesity‐associated illnesses .…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, systemic pifithrin-α administration considerably diminished P53 levels and ameliorated Akt phosphorylation in all peripheral tissues including adipose tissues and alleviated IR. 33 As Mdm2 protein functions as an E3 ubiquitin ligase that inhibits p53 transcriptional activation, the Mdm2 C305F mice are resistant to HFD-induced obesity and obesity-associated illnesses. 34 Our results showed that P53 protein levels were markedly elevated in the liver tissue induced by HFD for 12 weeks and PA incubation enhanced the expression of P53 in AML12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The masses of all three adipose tissue types were lower in p53 178C/C mice, with a more pronounced effect on iWAT, which showed smaller adipocytes compared with p53 wild-type or null mice ( Figure 2B). Given the various contrasting reports of BAT regulation by p53 (Krstic et al, 2018), we examined BAT mitochondria and the thermogenesis phenotype of p53 178C/C mice but did not observe significant differences, consistent with only a modest decrease in its mass .…”
Section: A Mouse Homolog Of a Lfs Mutation Reveals A Metabolic Phenotypementioning
confidence: 91%
“…Contrary to its role as a tumor suppressor, the sustained activation of p53 signaling has been linked to the development of insulin resistance and adiposity. Activation of p53 also contributes to the induction of inflammatory cytokines that can promote the initiation and progression of cancer …”
Section: Introductionmentioning
confidence: 99%
“…Activation of p53 also contributes to the induction of inflammatory cytokines that can promote the initiation and progression of cancer. [22][23][24] Another pathway that seems to associate obesity with cancer development is genetic instability. 25 Many studies have indicated that obesity-related modulations in DNA damage and/or repair pathways may be involved in obesity-induced genetic instability.…”
Section: Introductionmentioning
confidence: 99%